PERAN ACCOUNT OFFICER DALAM MENEKAN KREDIT BERMASALAH (Studi pada BPR di Kab .Grobogan ) - Endang Rusdianti; Paulus Wardoyo; Ani Setyarini (Universitas Semarang, 2018)
The research objective is to analyze the role of Account Officers in suppressing non-performing loans from the Rural Banks of Kabupaten Grobongan. The analysis relates to whether the role of the account officer influences the business of the banking sector in granting credit so that it can reduce problem loans. The proxy role of the account officer is the ability to analyze credit and supervision activities by considering customer development as a moderating variable. The method used is the MRA, SPSS 22. The data type is primary data obtained by questionnaire method on the variables of credit analysis, supervision, customer guidance and problem loans. The respondents were 70 Accounts from the BPR of Kabupaten Grobogan The results show that credit analysis and supervision have an effect on bad credit. Moderating variables are used to overcome bad credit, namely customer coaching as an effort to increase / weaken the relationship of credit analysis and supervision of bad credit. The result of coaching on credit analysis does not act as moderation but acts as a predictor. In relation to supervision, coaching acts as a quasi moderation and results are negative, which means that coaching actually weakens the influence of supervision.